Application Specific Sleep-Awake Strategy for Increasing Network Lifetime in Wireless Sensor Networks - Sinan Toklu; Mehmet Şimşek (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Wireless Sensor Networks (WSN) is a technology that provides distributed data collection. However, these networks have some limitations. The most important constraint is energy limitations. The lifespan of sensor nodes that run on small battery depends on the battery life. Although there are many studies in the field of energy efficiency to extend the life of nodes, enough improvement has not been obtained yet. The most basic way to achieve energy efficiency is to sleep and awake the nodes or clusters of nodes. In this study, we proposed an application specific method to wake up and sleep nodes in WSNs. In traditional strategy, the nodes in the cluster sense data and send it to the Cluster Head (CH), if CHs detect redundancy of some data; they remove the duplication and send it to the base station. This is causing energy loss. Our method puts some nodes to sleep state if there are similar data in a certain period. By this way, the life of the network is extended.